Minimizing Smes Problems in Nigeria for Economy Sustainability Using Quantitative Technique - Segun Kehinde; Chinonye Moses; Taiye Borishade; Michael Agarana; Fejiro Edewor; Dele-Dada Moyosoluwa; Nifemi Obembe (MultiTech Publisher, 2023)
Small and medium scale Enterprises (SMEs) are vital to the economic development and growth of every developing economy. As SMEs strive to boost the Nigerian economy, they are faced with multiple internal and external challenges. This study proposes a simple method of minimizing those internal and external problems faced by SMEs using Quantitative techniques. It was discovered that the proposed approach significantly minimizes SMEs problems in Nigeria for economy sustainability. This study recommends for government to innovate their policies in order to complement an ever evolving economy.